Intramolecular and Intermolecular Interactions of Protein Kinase B Define Its Activation In Vivo - Calleja, Véronique (Public Library of Science, 2007)
Protein kinase B (PKB/Akt) is a pivotal regulator of diverse metabolic, phenotypic, and antiapoptotic cellular controls and has been shown to be a key player in cancer progression. Here, using fluorescent reporters, we shown in cells that, contrary to in vitro analyses, 3-phosphoinositide–dependent protein kinase 1 (PDK1) is complexed to its substrate, PKB. The use of Förster resonance energy transfer detected by both frequency domain and two-photon time domain fluorescence lifetime imaging microscopy has lead to novel in vivo findings. The preactivation complex of PKB and PDK1 is maintained in an inactive state through a PKB intramolecular interaction between its pleckstrin homology (PH) and kinase domains, in a “PH-in” conformer. This domain–domain interaction prevents the PKB activation loop from being phosphorylated by PDK1. The interactive regions for this intramolecular PKB interaction were predicted through molecular modeling and tested through mutagenesis, supporting the derived model. Physiologically, agonist-induced phosphorylation of PKB by PDK1 occurs coincident to plasma membrane recruitment, and we further shown here that this process is associated with a conformational change in PKB at the membrane, producing a “PH-out” conformer and enabling PDK1 access the activation loop. The active, phosphorylated, “PH-out” conformer can dissociate from the membrane and retain this conformation to phosphorylate substrates distal to the membrane. These in vivo studies provide a new model for the mechanism of activation of PKB. This study takes a crucial widely studied regulator (physiology and pathology) and addresses the fundamental question of the dynamic in vivo behaviour of PKB with a detailed molecular mechanism. This has important implications not only in extending our understanding of this oncogenic protein kinase but also in opening up distinct opportunities for therapeutic intervention.